Manajemen Sumber Daya Manusia Generasi Z di Lembaga Pendidikan Dasar - Wijayanti, Intan (Prodi PGMI STAI Al-Akbar Surabaya, 2025)
The development of digital technology has given birth to a new generation known as Generation Z, which has unique characteristics such as high technological skills, a need for work flexibility, and an orientation towards efficiency. Thisgeneration is starting to dominate elementary education institutions as educators and educational personnel (PTK),thus demanding a different and more adaptive approach to human resource management (HRM). This study aims toexamine the HRM strategy for PTK from Generation Z in elementary education institutions, as well as identify the challenges faced. The method used is a literature review with an interpretive approach to various relevant literature. The results of the study indicate that managing Generation Z HR requires a digital recruitment strategy, technology-based training, a rapid evaluation system, collaborative leadership, and open communication. The main challenges faced by educational institutions include dependence on technology, a tendency towards instant gratification, low loyalty, and limitations in teamwork. Therefore, elementary educationinstitutions need to adopt innovative and humanistic HRM to optimize the potential of Generation Z in improving the quality of education.